Adoption status of direct seeded rice technology by the farmers of Punjab - Kamboj, Ramandeep; Singh, Dharminder; Kaur, Lakhwinder (Indian Journal of Extension Education, 2021)
Direct-seeded rice (DSR) is a possible alternative to conventional puddled transplanted rice, where rice crop is seeded directly in non-puddled fields. The study was conducted to ascertain the adoption status of recommended practices of DSR. Personal interviews were conducted to collect data from randomly selected 210 farmers from three districts representing different agro-climatic regions of Punjab. Study revealed that selected farmers had adopted DSR on 49.20 per cent of their total area under paddy cultivation. Slightly higher number of selected farmers had adopted Tar-Wattar, a new technique of DSR over dry soil method. Only 18.52 per cent respondents had applied first irrigation as per recommendations of Tar-Wattar method, whereas majority (67.59%) had applied first irrigation before 21days. 26.67% farmers had adopted most suitable variety PR-126 and sown it at recommended time. However, in case of other varieties, majority of farmers did not follow recommended time of sowing. A smaller number of farmers have applied zinc, iron and sulphur fertilizers to ameliorate micro nutrient deficiencies. Average yield of others varieties and PR 126 were found to be nearly identical, but due to lesser cost of cultivation in DSR as compared to transplanted rice, adopter farmers’ fetched higher net return.